2008
DOI: 10.1111/j.1537-2995.2007.01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Overnight or fresh buffy coat–derived platelet concentrates prepared with various platelet pooling systems

Abstract: The quality of PCs depended on whether PCs were prepared from fresh or overnight-stored whole blood and on the used PLT pooling system. The main difference between fresh and o/n PCs was the PLT count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 30 publications
3
33
2
1
Order By: Relevance
“…However none of the metabolic parameters between two groups were statistically significant even after 5 days of storage. Dijkstra-Tiekstra et al [10] found that the overnight PC higher pCO2, and lactate concentration and lower pH, pO2, glucose concentration, CD62P expression (until day 5). We did not measure the lactate concentration but rest of the findings are comparable with our results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However none of the metabolic parameters between two groups were statistically significant even after 5 days of storage. Dijkstra-Tiekstra et al [10] found that the overnight PC higher pCO2, and lactate concentration and lower pH, pO2, glucose concentration, CD62P expression (until day 5). We did not measure the lactate concentration but rest of the findings are comparable with our results.…”
Section: Discussionmentioning
confidence: 98%
“…In our study 10.87 % more platelets were concentrated in stored BC compared to fresh BC. Dijkstra-Tiekstra et al [10] explained in their study that the overnight platelet concentrate (PC) showed higher PLT count (approx. 460 9 10 9 /PC vs. approx.…”
Section: Discussionmentioning
confidence: 99%
“…The apparently lower platelet content immediately after donation translates into lower platelet numbers per platelet concentrate, as shown by a study [34] that compared the composition and storage of buffy coat-derived platelet concentrates from whole blood processed into platelet concentrates 4 to 6 hours after collection, with those from whole blood stored overnight. Platelet content was about a third lower when made from buffy coats at the day of collection rather than after overnight hold, irrespective of the 4 buffy coat pooling systems used in this study.…”
Section: Effect Of Whole Blood Holding Time On the Quality Of Buffy Cmentioning
confidence: 95%
“…All blood products used in this study were derived from donors who gave consent for using part of their whole blood donation for research purposes. In short, plasma was added to a residual buffy coat pool, which is the remaining material after platelet production [9], via a used leukoreduction filter in opposite direction to increase the WBC count (Compostop, Fresenius Hemocare; Emmer Compascuum, the Netherlands). The used plasma and residual buffy coat pool was derived from whole blood collection of one day before.…”
Section: Preparation Of the Wbc-enriched Productmentioning
confidence: 99%